"I thought I was going to die there:" Socio-political contexts and the plight of undocumented Latinx in the COVID-19 pandemic - Carol Cleaveland; Myeong Lee; Constance Gewa (Elsevier, 2023)
Since the beginning of the COVID-19 pandemic, certain U.S. population groups have suffered higher rates of infection and mortality than whites, including Latinx. Public health officials blamed these outcomes on overcrowded housing and work in essential industries prior to the vaccine's availability. We sought to illuminate the lived experience of these factors through a qualitative study of undocumented Latinx immigrant workers in the secondary economy (n ​= ​34). This study focuses on the intersectionality of social locations for undocumented Latinx immigrants living in a relatively affluent suburb and working in the construction and service sectors prior to the pandemic. Their narratives revealed how the pandemic created financial precarity through prolonged periods of unemployment and food insecurity. Workers described worry over unpaid bills, and potentially catastrophic episodes in which they treated severe COVID-19 with home remedies. Long spells of unemployment, food insecurity, inability to pay bills and lack of access to healthcare emerged because of socio-political contexts including the nature of low-wage labor and lack of a safety net.